Soybean yield potential influenced by soil phosphorus content and row spacing - Ventimiglia, Luis Alberto; Costa, José Antonio; Thomas, André Luís; Pires, João Leonardo Fernandes (Pesquisa Agropecuaria Brasileira, 1999)
The experiment was performed during the 1994/95 growing season at the EEA/UFRGS, in Eldorado do Sul, RS, Brazil, in a dark red Podzolic soil (Rhodic Paleudult). The objective was to evaluate the soybean potential yield at the growth stages R2 (flowering), R5 (beginning of pod filling) and R8 (maturity). The treatments were arranged in subplots in a randomized complete block design, and consisted of two soil P levels (3 and 15 ppm), and two row spacings (20 and 40 cm). The early, determinate cultivar OCEPAR 14 was used. On the average of the treatments, potential yield in R2 was of 18 t/ha and of 10 t/ha in R5, and the final yield, in R8 of 4.6 t/ha. The treatment of 15 ppm of P reached greater potential yield in the three growth stages, due to less flower and pod abortion. The row spacing of 20 cm showed greater potential yield at the growth stages evaluated, but the percentage of yield reduction due to flower and pod abortion were similar.